Indoor Pool Game and Substance Abuse as Trajectories to Students’ Academic Procrastination: The Mediation Role of Self-Regulation - Gita, Dinaol Urgessa; Koya, Amanuel Tadesse; Worku, Berhanu Nigussie (Frontiers in Psychology, 2022)
Abstract Background: Over the last decade, indoor pool games and substance abuse became remarkable emerging addictive behavior among adolescent university students. With the failure of educational quality and retention of learners, boomerangs around university local environment in line with students learning culture was not considered in many countries including Ethiopia. Thus, this study was aimed to examine the trajectory and contribution of an indoor pool game and substance abuse to students' academic procrastination as determinants of quality education. Methods: A sequential explanatory mixed-methods design was employed. Self-reporting questionnaires, interview guides, and observation checklists were used to collect data. Self-reporting items for Indoor pool games and substance abuse questionnaires were adapted from European School Survey Project on Alcohol and Other Drugs (ESPAD, 2015). The academic procrastination questionnaire was adapted from Yockey’s (2016) short scale and self-regulation items were adapted from Chen and Lin (2018). By using simple random sampling techniques, 237 undergraduate university students were selected for obtaining quantitative data and using purposive sampling, 12 interviewees’ were selected to collect qualitative data. SPSS AMOS version 25 was used to compute multiple mediation path analysis. Hayes' Macro process Model was used. Further, the thematic content analysis method was employed for the qualitative data. Results: A direct path analysis was established between in-door pool games, substance abuse, and academic procrastination. The path analysis model indicated that in-door pool games did not significantly predict academic procrastination. Moreover, substance abuse significantly predicted academic procrastination. In addition, self-regulation had a partial mediating effect on the relationship between indoor pool games(IPG), Substance Abuse(SA), and Academic procrastination(AP). Conclusion: This study concluded that in-door pool games and substances situated around the university's local environment were found to be contributors and trajectories to students' academic procrastination which in turn affected the quality of education. Keywords: Academic procrastination behavior; Drug abuse; Indoor pool game; Mediation; University students